Analysis Of Cognitive Difficulties Of Junior High School Students In Solving The Problem Of Pythagorean Theorem - Ardhiansah, Dian; Muhtadi, Dedi; Apiati , Vepi (Koordinat Jurnal MIPA, 2025)
This study aims to analyze students' difficulties in solving problems related to the Pythagorean Theorem and identify the causative factors. The qualitative case study approach was used by involving 30 grade VIII students from SMP Negeri 8 Tasikmalaya who were selected based on the complexity of the mistakes they made. The research instruments included written tests, in-depth interviews, and classroom observations. The data were analyzed using thematic analysis to identify patterns of difficulty and their causative factors. The results showed four main categories of students' difficulties, namely: (1) conceptual errors (70% difficulty identifying the oblique side of a right triangle); (2) procedural errors (65% did not follow the calculation steps correctly); (3) errors in interpreting story questions (60% cannot convert problem information into mathematical models); and (4) math anxiety (50% feel nervous about facing problems with large numbers). The causative factors include monotonous teaching methods, lack of use of teaching aids, and low motivation to learn. The discussion highlighted the importance of interactive and contextual learning to overcome these difficulties. Recommendations include the use of visual media, the integration of technology to reinforce concepts, and approaches that are appropriate to students' learning styles. This research emphasizes the need for innovative pedagogical strategies to improve students' understanding and problem-solving skills